“I Asked for It”: How Women Experience Stigma in Their Transition from Being Infertile to Being Mothers of Multiples through Assisted Reproductive Technologies - Kaur, Navjotpal; Ricciardelli, Rosemary (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
Although researchers agree that infertility is a stigmatizing attribute, scholars are largely divided in their criticism of assisted reproductive technology (ART). Some criticize the increased and invasive medical interventions as disempowering women, whereas others argue that ARTs empower women by protecting their right to reproduce as they see fit. Research on the stigmatization of infertility and ART in the context of mothers of multiples is conspicuously missing from the literature a notable lacuna in knowledge given ARTs are more likely to result in multiple births. Drawing on in-depth semi-structured interviews with twenty-three mothers of multiples, we show how these women interpret the stigma of first being “infertile” to then being “artificially” fertile to becoming mothers of multiples. Interviewees reveal that despite the agential freedom they have in regard to choice in fertility treatments, they feel disempowered, even judged, when undergoing ART. Focusing on women who had twins or triplets after undergoing ART, we show how the alleged “empowerment” bestowed on women by providing the choice to use ART can transform into disempowerment.